Collaboration Strategy Based on Conflict Resolution for Flatness Actuator Group. (17th April 2021) - Yan, Zhu-Wen; Wang, Bao-Sheng; Bu, He-Nan; Pan, Long; Hong, Lei; Zhang, Dian-Hua; Wang, Hong-Yu; Lv, Dong-Sheng
Abstract : During the flatness control process, there are frequently some uncoordinated regulating behaviors in the flatness actuator group. This has a bad influence on the flatness control accuracy and the flatness control efficiency. Therefore, a collaboration strategy based on conflict resolution for the flatness actuator group has been proposed in this paper. First of all, the feature of flatness measurement value is extracted through establishing the actual flatness condition discriminating factor. After that, the coordination cooperation that is appropriate to the actual flatness condition is developed for the flatness actuator group. Finally, the optimal adjustment of the actuator population is solved by the coordinated algorithm of Topkis-Veinott and genetic algorithm collaborative optimization. The collaboration strategy proposed in this paper has been successfully applied to a flatness control system of a 1450 mm five-stand cold rolling mill.